2019
DOI: 10.21037/acs.2019.08.07
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for type A intramural hematoma: a systematic review of clinical outcomes

Abstract: Background: Management of type A intramural hematoma (IMH) remains controversial, with opinions divided as to whether patients should be treated with early aggressive surgery or a more conservative approach. The present systematic review aims to evaluate the mortality and morbidities following surgery for type A IMH. Methods: Electronic searches were performed on five databases from dates of inception to December 2018. All studies with surgical outcomes for type A intramural hematoma were identified by two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A recently published multi-center study had demonstrated that TEVAR is a safe alternative to open repair, with no 30-day mortality and a low re-intervention rate of only 6%. Post-operative neurological complications developed in two (11.1%) patients and renal/respiratory failure in one (5.6%) ( 10 ), and these numbers were substantially lower than open repair, which were reported to be around 12.9%~31.7% and 9.9% ~ 50.5%, respectively ( 4 , 16 18 ). In our study, the short-term composite morbidities were significantly higher for patients after open repair, consisting of post-operative stroke, renal failure and bleeding etc.…”
Section: Discussionmentioning
confidence: 90%
“…A recently published multi-center study had demonstrated that TEVAR is a safe alternative to open repair, with no 30-day mortality and a low re-intervention rate of only 6%. Post-operative neurological complications developed in two (11.1%) patients and renal/respiratory failure in one (5.6%) ( 10 ), and these numbers were substantially lower than open repair, which were reported to be around 12.9%~31.7% and 9.9% ~ 50.5%, respectively ( 4 , 16 18 ). In our study, the short-term composite morbidities were significantly higher for patients after open repair, consisting of post-operative stroke, renal failure and bleeding etc.…”
Section: Discussionmentioning
confidence: 90%
“…However, it is also important for clinicians to consider IMH as a distinct entity from classical dissections that may benefit even further from maximal medical therapy and subsequent expectant management with delayed surgery or surgery as needed. Patient characteristics and presentation play a large role in making this determination with differing recommendations based on geographical location [11]. The patient in our case benefitted from early, aggressive blood pressure control leading to a stable hemodynamic status that precluded the need for any surgical intervention during their admission.…”
Section: Discussionmentioning
confidence: 90%
“…A systematic review of surgical outcomes of ATAIMH identified acceptable risks of postoperative mortality. However, significant heterogeneity exists in the outcomes between Western and Eastern countries (14). Western guidelines recognize IMH as a subset of acute aortic syndrome, and therefore advocate urgent surgery for ATAIMH.…”
Section: Discussionmentioning
confidence: 99%